Teaching experience of physical education and sports teachers in the new program (second generation) Scan search conducted on the professors of the secondary city of El bayand Algeria - قزقوز, محمد (المؤتمر الدولي الخامس بجامعة يلدز تكنيكول –إسطنبول - حول : " للعلوم الاجتماعية, 2018)
The study aimed to study the teaching knowledge of a professor of physical education and sports in light of the new curriculum proposed by the Algerian Ministry of Education (the second generation) by knowing the extent of experience and knowledge of the teachers of the average physical education and sports in the city of al-Bayadh, Algeria under the new curriculum and in order to answer The following questions: To what extent does the professor of physical education and sports know the experiences of teaching the new curriculum? For this purpose, we imposed - a professor of physical education and sports with teaching experiences above average to teach the new curriculum, and for this the study was carried out on (20) teachers from the averages of the city of al-Bayadh, Algeria. The sample is intended. For this purpose, we used the percentage ratios and the Ka-2 test to study the phenomenon, which is a case characterized by sincerity, and after collecting the results and treating them, we came to the following: - That the professor of physical and sports education has teaching experiences and knowledge above average, which is consistent with previous studies and theoretical studies. In the end, we recommend that: - Facilitating the university for students in physical education and sports according to the needs of the Ministry of Education - Holding training courses for teachers where the new curriculum is under study.
Keywords: knowing the extent of experience and knowledge